2020
DOI: 10.20546/ijcmas.2020.910.444
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Distribution of Coconut Diseases in Tamil Nadu, India

Abstract: Coconut is an important plantation crop with many decades of life span ,suffers from numerous diseases incited by fungi ,bacteria, virus, viriod and phytoplasma leads to drastic reduction in yield. Roving survey was conducted in five major coconut growing districts of Tamil Nadu viz., Coimbatore, Tirupur, Theni, Tirunelveli and Kanyakumari districts during 2014-2019 for assessing the incidence of important diseases of coconut .The fungal diseases viz., bud rot, basal stem rot, stem bleeding, leaf blight and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It is reported that at Vepangulam, Tamil Nadu disease intensity in East Coast Tall coconut was maximum in December (40.5 %) and minimum in June (23.9 %). Surveys conducted by Esakkimuthu et al (2020) in Tamil Nadu showed that Avalchinnampalayam, Angalakuruchi and Kalliyapuram villages of Coimbatore district had maximum disease incidence and the severity was more in dwarf varieties compared to tall varieties. Study conducted in plantation crop based cropping system plots of Wayanad district of Kerala to assess different diseases for their incidence during different seasons revealed that in Coconut, grey leaf blight was found to be the most severe one with a disease incidence of 98.6% incidence during NE monsoon (John et al 2011).…”
Section: Status and Distributionmentioning
confidence: 98%
See 3 more Smart Citations
“…It is reported that at Vepangulam, Tamil Nadu disease intensity in East Coast Tall coconut was maximum in December (40.5 %) and minimum in June (23.9 %). Surveys conducted by Esakkimuthu et al (2020) in Tamil Nadu showed that Avalchinnampalayam, Angalakuruchi and Kalliyapuram villages of Coimbatore district had maximum disease incidence and the severity was more in dwarf varieties compared to tall varieties. Study conducted in plantation crop based cropping system plots of Wayanad district of Kerala to assess different diseases for their incidence during different seasons revealed that in Coconut, grey leaf blight was found to be the most severe one with a disease incidence of 98.6% incidence during NE monsoon (John et al 2011).…”
Section: Status and Distributionmentioning
confidence: 98%
“…Johnson et al (2014) reported that Lasiodiplodia has become a major problem in coconut growing districts of Tamil Nadu viz., Coimbatore, Erode, Dindigul, Tirunelveli and Kanyakumari which lead to yield reduction of 10-62(1) March, 2024] Keerthana Jayarajan and others 25%. The disease is endemic in Sencherimaali, Thanthoni and Karapadi villages of Tirupur district and Odayakulam and Kaliapuram of Coimbatore district (Esakkimuthu et al 2020). Survey conducted by Neeraja et al (2020) in West Godavari and East Godavari districts of Andhra Pradesh indicated that the disease incidence was more in Jangareddygudem village of West Godavari (25.8%) and in Mamidikuduru village of East Godavari (25.5%).…”
Section: Status and Distributionmentioning
confidence: 98%
See 2 more Smart Citations
“…The nuts become desiccated, shrunken, deformed and dropped prematurely. In the leaves, this pathogen causes the disease "leaf blight", drying leaves from tip downwards, inducing a charred or burnt appearance, more evident on lower fronds [25]. Lasiodiplodia theobromae causes significant monetary losses in the coconut industry in India.…”
Section: Coconut Pests and Diseasesmentioning
confidence: 99%